A Southeastern Turkic Liturgical Poem in two Lithuanian-Polish-Belarusian Tatar Manuscripts: The Link to Aḥmad Yasavī Tradition - Jankowski, Henryk (Rocznik Orientalistyczny/Yearbook of Oriental Studies, 2026)
The aim of this paper is to edit a poem of the zikr genre found in two Lithuanian-Polish- Belarusian Tatar manuscripts critically and to demonstrate that it belongs to the Aḥmad Yasavī tradition. Among the Turkic zikrs which have so far been identified in this literature, this is the only one which exhibits Southeastern Turkic or Chaghatay features. However, at the same time it also reveals Turkish traits. The article tries to explain this diversity of features. The Chaghatay source of this poem was found in a ḥikmat collection published in Istanbul in 1881/1882 attributed to Aḥmad Yasavī. There is also indirect evidence for the existence of this zikr in a manuscript held in a private collection in Central Asia, but it is unavailable for research and was published in a popular book. The article also discusses the questions of language, literature and style relating to this poem. Attempt was also made to show that there is no evidence for any Sufi activity among Lithuanian- Polish-Belarusian Tatars in the past and that the Sufi elements were transplanted through Turkic manuscripts without any intentional endeavour to adopt Sufism as a doctrine.